1999
DOI: 10.1164/ajrccm.159.5.9806008
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Recruitment by Interleukin-17 into Rat Airways In Vivo

Abstract: We determined whether neutrophil recruitment induced by the T-lymphocyte cytokine, interleukin-17 (IL-17) is modulated by tachykinins in airways in vivo. Cell recruitment into airways was induced by either human (h) IL-17 (1 microgram) or rat (r) IL-1beta (2. 5 ng), instilled intratracheally in rats (n = 5 to 7). Six hours after instillation, hIL-17 (3.1 +/- 1.2 x 10(6) cells/ml) and rIL-1beta (4.1 +/- 0.5 x 10(6) cells/ml), respectively, induced a significant and selective increase in neutrophil count in bron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(72 citation statements)
references
References 34 publications
2
70
0
Order By: Relevance
“…When compared with its family member IL-17, IL-17B is about 10 time less potent in inducing PMN infiltration (Ref. 16 and data not shown).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…When compared with its family member IL-17, IL-17B is about 10 time less potent in inducing PMN infiltration (Ref. 16 and data not shown).…”
Section: Discussionmentioning
confidence: 97%
“…More recently, IL-17 has been implicated in allergic skin immune responses (14), neutrophil recruitment during airway inflammation (15,16), cardiac and renal allograft rejection (17)(18)(19), and granulopoiesis (21,22). In addition, it has been found to up-regulate nitric oxide production in human osteoarthritic cartilage and inflammatory cytokine production by rheumatoid arthritis synoviocytes (23,24), to stimulate osteoclastogenesis and the expression of several genes associated with inflammation and cartilage degradation in human chondrocytes (25)(26)(27)(28), and to induce ICAM-1 expression in human bronchial epithelial cells (29).…”
mentioning
confidence: 99%
“…This hypothesis was initially based merely on plain experimental studies that documented the neutrophil mobilising potential of IL-17A protein in animal airway models in vivo plus models of human bronchial epithelial and venous endothelial cells in vitro [15][16][17]. In essence, the results of these early experimental studies indicated that IL-17A recruits and accumulates neutrophils indirectly into the airways by inducing the transcription and release of neutrophil mobilising cytokines from structural airway cells ( fig.…”
Section: Original Hypothesis On Neutrophil Accumulationmentioning
confidence: 99%
“…The intracellular pathways leading to this type of response appear to involve MAP kinases, even though there is conflicting data on the specific type of MAP kinase involved in human bronchial epithelial cells (74,75). Of particular interest in the context of neutrophilic airway inflammation is the fact that hIL-17 stimulates human venous endothelial cells, bronchial fibroblasts and macrophages to release IL-6 and IL-8 as well, even though the functional significance of these effects remains to be proven (46,76,77).…”
Section: Stimulation With Il-17 Causes Expression Of Neutrophilmobilimentioning
confidence: 99%